A comparative study between the (deaf and dumb) and healthy level of learning some basic skills in the game of volleyball. - Laabi, Shireen (Journal of Physical Education, 2010)
Section I: Included this section on the Introduction and the importance of research with regard to the subject of the researcher discussed with regard to the sensory capabilities and owned by the human body and the loss of such capacity or of the person making the sensory disabled, and the problem of research, the researcher asked about the loss one of these sensory capabilities is strengthen or weaken the other senses? Will help to support or weaken the learning process? Therefore, the researcher proceeded to the discovery of the effects of loss of hearing ability and speech, with a mechanism of communication at the level of learning, including the door in the objectives of the research was the development of curriculum for some of the basic volleyball skills and to study the impact of the plane that the curriculum at the level of learning healthy, deaf and dumb, and the researcher that there were random differences are not statistically significant between the level of learning some basic skills in volleyball between the deaf and dumb and healthy at the end of this section, according to the researcher and the research sample the venue for the trial and the date of the experiment. Section II: This section studies the theory that the researcher, which addressed the issue Hearing disability and going on around him. Part III: In this section addressed to the researcher, the research method used to achieve the objectives and Guess, and sample tests that were applied by the proposed approach, and also the actions of the field work and a description of the research and testing the proposed approach for the rehabilitation of self-confidence and levels of statistical methods used by the researcher to address the raw results obtained from tests . Part IV: After the statistical treatment of results by the researcher, the presentation and analysis and discussion of the results of this section. Part V: In the light of the findings of the researcher of the results in section IV, n introduced by the conclusions of which were identical to the set of assumptions to solve the problem before the search, in the light of these conclusions, recommended some of the recommendations in order to give the subject of self-confidence due importance by the staff side Sports.